The Forgotten Hemodynamic (PCO2 Gap) in Severe Sepsis - Zouheir Ibrahim Bitar; Ossama Sajeh Maadarani; AlAsmar Mohammed El-Shably; Ragab Desouky Elshabasy; Tamer Mohamed Zaalouk (Critical Care Research and Practice)
Background. Central venous-arterial carbon dioxide difference (PCO2 gap) can be a marker of cardiac output adequacy in global metabolic conditions that are less affected by the impairment of oxygen extraction capacity. We investigated the relation between the PCO2 gap, serum lactate, and cardiac index (CI) and prognostic value on admission in relation to fluid administration in the early phases of resuscitation in sepsis. We also investigated the chest ultrasound pattern A or B. Method. We performed a prospective observational study and recruited 28 patients with severe sepsis and septic shock in a mixed ICU. We determined central venous PO2, PCO2, PCO2 gap, lactate, and CI at 0 and 6 hours after critical care unit (CCU) admission. The population was divided into two groups based on the PCO2 gap (cutoff value 0.8 kPa). Results. The CI was significantly lower in the high PCO2 gap group (P=0.001). The high PCO2 gap group, on admission, required more administered fluid and vasopressors (P=0.01 and P=0.009, respectively). There was also a significant difference between the two groups for low mean pressure (P=0.01), central venous O2 (P=0.01), and lactate level (P=0.003). The mean arterial pressure was lower in the high PCO2 gap group, and the lactate level was higher, indicating global hypoperfusion. The hospital mortality rate for all patients was 24.5% (7/28). The in-hospital mortality rate was 20% (2/12) for the low gap group and 30% (5/16) for the high gap group; the odds ratio was 1.6 (95% CI 0.5–5.5; P=0.53). Patients with a persistent or rising PCO2 gap larger than 0.8 kPa at T = 6 and 12 hours had a higher mortality change (n = 6; in-hospital mortality was 21.4%) than patients with a PCO2 gap of less than 0.8 kPa at T = 6 (n = 1; in-hospital mortality was 3%); this odds ratio was 5.3 (95% CI 0.9–30.7; P=0.08). The PCO2 gap had no relation with the chest ultrasound pattern. Conclusion. The PCO2 gap is an important hemodynamic variable in the management of sepsis-induced circulatory failure. The PCO2 gap can be a marker of the adequacy of the cardiac output status in severe sepsis. A high PCO2 gap value (>0.8 kPa) can identify situations in which increasing CO can be attempted with fluid resuscitation in severe sepsis. The PCO2 gap carries an important prognostic value in severe sepsis.